Hubungan Pelaksanaan Peran Keluarga dengan Kejadian Stunting pada Balita di Kecamatan Arjasa, Jember - Umari Hasniah Rahmawati; Latifa Aini S; Hanny Rasni (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
A family has an important role to meet the nutritional intake of toddlers since a family has a full decision to nurture and take care of the toddlers. However, the case of stunting in Jember Regency still has a higher case compared to other regencies. The objective of this research was to analyze the relationship between the implementation of family role and the case of stunting in toddlers in Arjasa Subdistrict, Jember regency. The research also used a cross sectional research design with cluster random sampling technique. The data collection was conducted by providing a FAD (Family Assessment Device) questionnaire used to identify the family roles, while the height was measured by length board and microtoise. The chi-square test was employed to analyze between the variables of family role and stunting case. According to the analysis result of 117 respondents, there were 7.7%, 99% and 7.7% for each category of good, moderate and less in the family role, whereas for the stunting case, there were 76.1% having stunting and 23.9% not stunting. The findings of this research indicated that there was a relationship between the implementation of family role and the stunting case (χ2 = 9.78; p-value = 0.002), in which the implementation of family role in the good category had 7.81 times for a chance of stunting (OR = 7.81; 95% CI = 1.81-33.762). at last, this research showed the importance of improving the family role by involving the family to meet the daily nutritional intake of toddlers so as the stunting case can diminish.